Modifications to ideal stability by kinetic effects in NSTX. (30th October 2015) - Berkery, J.W.; Sabbagh, S.A.; Bell, R.E.; Gerhardt, S.P.; LeBlanc, B.P.; Menard, J.E.
Abstract: Marginal stability points of global modes during high plasma pressure operation in the National Spherical Torus Experiment (NSTX) device can be found by computing kinetic modifications to ideal magnetohydrodynamic limits on stability. Calculations with theDCON code for nearly five thousand experimental equilibria show that previous estimates of the no-wall limit (below which the ideal kink/ballooning mode would be stable even without conducting structure surrounding the plasma) on the plasma beta (a ratio of plasma pressure to magnetic pressure) and internal inductance (a measure of the current profile peakedness) were relatively accurate, though about 10% low. The no-wall beta limit also decreased with increasing aspect ratio and increasing broadness of the pressure profile, and these dependencies have implications for the upgrade to NSTX which has a larger aspect ratio and new neutral beams that may increase the broadness of pressure and current profiles. Kinetic modifications to ideal limits calculated with the Modifications to Ideal Stability by Kinetic effects (MISK ) code are further validated by detailed comparison with experimental results from NSTX. In several discharges the code predicts a transition from damping of the mode to growth as the time approaches the experimental time of marginal stability to the resistive wall mode (RWM). The main stabilization mechanism is through rotational resonances with the motions of thermal particles in the plasma, though energetic particles also contribute to stability, and it is often when the plasma rotation falls in between these resonances that the RWM was destabilized in NSTX. The calculations are found to be slightly affected by changing the assumed magnetic structure of the mode as well. These validations are important for real-time assessment of stability limits for disruption avoidance, and reliable projections of the stability of future devices.